ENGINEER WP2 SS1 PhotogrammetryCloseRange NikonD780 - Skarlatos, Dimitrios; Vlachos, Marinos; Hadjipetrou, Stylianos; Agapiou, Athos (My University, 2024)
This dataset was created during ENGINEER project activities and is accessible only upon user request and approval by the responsible national authority of Cyprus, namely the Department of Antiquities. The dataset pertains to close-range photogrammetry data acquired using a Nikon D780 camera.